2011
DOI: 10.1007/s00101-011-1872-5
|View full text |Cite
|
Sign up to set email alerts
|

Extrakorporale Membranoxygenierung und schweres Schädel-Hirn-Trauma

Abstract: Veno-venous extracorporeal membrane oxygenation (ECMO) may be lifesaving in multiple injured patients with acute respiratory distress syndrome (ARDS) due to chest trauma. To prevent circuit thrombosis or thromboembolic complications during ECMO systemic anticoagulation is recommended. Therefore, ECMO treatment is contraindicated in patients with intracranial bleeding. The management of veno-venous ECMO without systemic anticoagulation in a patient suffering from traumatic lung failure and severe traumatic brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A case report evaluated the management of venovenous ECMO without systemic anticoagulation in a patient with severe lung and brain injuries. [ 17 ] Another case series reported that patients with traumatic brain injury who received ECMO support had a relatively high survival rate and a low rate of neurologic sequelae. [ 18 ] Even patients with intracranial hemorrhage who required craniotomy exhibited a more favorable outcome with the use of ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…A case report evaluated the management of venovenous ECMO without systemic anticoagulation in a patient with severe lung and brain injuries. [ 17 ] Another case series reported that patients with traumatic brain injury who received ECMO support had a relatively high survival rate and a low rate of neurologic sequelae. [ 18 ] Even patients with intracranial hemorrhage who required craniotomy exhibited a more favorable outcome with the use of ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…ECMO has been proved to be an rescue therapy when conventional methods are ineffective. ECMO was also reported to be effective in polytraumatic patients combining pulmonary contusion and other organ damage including bronchial rupture [2,4], endobronchial hemorrhage [5], blunt abdominal trauma (BAT) with internal bleeding necessitating exploratory laparotomy [6], or traumatic brain injury [7-10]. However, the use of ECMO on patients with a preexisting bleeding risk without need of immediate operation is still rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…TBI was previously contraindicated for ECMO due to the heightened risk of intracranial hemorrhage from systemic anticoagulation [ 30 , 60 , 61 ]. Recently, advancements in procedures have mitigated this bleeding risk, including low-dose anticoagulation [ 29 , 33 ], delayed anticoagulation (after 48–72 h) [ 9 , 37 ], heparin-free application [ 36 , 41 ], and improved heparin-binding circuits [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Positive outcomes have been observed even in TBI patients undergoing craniotomy for intracranial hemorrhage [ 62 ]. Although concerns exist about possible worsening of intracranial hemorrhage with systemic anticoagulation during ECMO [ 60 ], a study conducted by Parker et al [ 14 ] supported the use of VV ECMO therapy in TBI patients, with 6 out of 13 patients receiving systemic anticoagulation, as no deterioration in intracranial hemorrhage was observed. In a study by Kruit et al [ 15 ], 19 TBI patients were supported on ECMO, with 12 of them receiving anticoagulation.…”
Section: Discussionmentioning
confidence: 99%